Import Demand Elasticities and Trade Distortions - Kee, Hiau Looi (2012)
This paper provides a systematic estimation of import demand elasticities for a broad group of countries at a very disaggregated level of product detail. We use a semiflexible translog GDP function approach to formally derive import demands and their elasticities, which are estimated with data on prices and endowments. Within a theoretically consistent framework, we use the estimated elasticities to construct Feenstra's (1995) simplification of Anderson and Neary's trade restrictiveness index (TRI). The difference between TRIs and import-weighted tariffs is shown to depend on the tariff variance and the covariance between tariffs and import demand elasticities.